2021
DOI: 10.3390/nano11071709
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graphene Oxidation on Interaction Energy and Interfacial Thermal Conductivity of Polymer Nanocomposite: A Molecular Dynamics Approach

Abstract: Interfacial characteristics of polymer nanocomposites represent a crucial aspect to understand their global properties and to evaluate the interaction between nanofillers and matrix. In this work we used a molecular dynamics (MD) approach to characterize the interfacial region at the atomistic scale of graphene-based polymer nanocomposites. Three different polymer matrixes were considered, polylactic acid (PLA), polypropylene (PP) and epoxy resin (EPO), which were reinforced with three types of graphene filler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…RNEMD simulations have demonstrated that functionalization, both noncovalent and covalent, may improve ITC between 2DM and polymer matrix due to stronger interfacial interactions and greater phonon vibrational match, even though it degrades the TC of pristine graphene by orders of magnitude. [ 228 ] This effect is presented in Figure 16A, and it has been experimentally verified when coupling h‐BN to silane agents to improve epoxy's TC, achieving an enhancement of more than 500% at 30 wt%. [ 229 ]…”
Section: Thermal Propertiesmentioning
confidence: 82%
“…RNEMD simulations have demonstrated that functionalization, both noncovalent and covalent, may improve ITC between 2DM and polymer matrix due to stronger interfacial interactions and greater phonon vibrational match, even though it degrades the TC of pristine graphene by orders of magnitude. [ 228 ] This effect is presented in Figure 16A, and it has been experimentally verified when coupling h‐BN to silane agents to improve epoxy's TC, achieving an enhancement of more than 500% at 30 wt%. [ 229 ]…”
Section: Thermal Propertiesmentioning
confidence: 82%
“…The interfacial thermal resistance exhibits the same behavior/tendency in the three polymers (PLA, PP, and epoxy): graphene > rGO ≈ GO. 86 It was also observed that the presence of functional groups in the graphene, in the form of oxidation (hydroxyl and oxirane groups), increased the interfacial thermal conductivity.…”
Section: Thermal/electrical Conductivity Of 2d Nanosheet Filled Pncsmentioning
confidence: 99%
“…More specifically, the remarkable engineering properties of graphene/epoxy nanocomposites have attracted the interest of both researchers and stakeholders. Therefore, such nanocomposites have been utilized to further improve the mechanical properties of traditional carbon fiber/epoxy composites by fabricating carbon fiber/graphene/epoxy hybrid composites [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Apart from structural materials, graphene-based materials find application in various fields such as ultra-narrow sensors for biomolecules detection [ 11 ] and electrochemical sensors for detecting harmful chemicals released into the air from flame retardants [ 12 ], modulators and detectors fabricated as a two-dimensional material [ 13 ], and water-treatment applications to clean-up impurities in water [ 14 ].…”
Section: Introductionmentioning
confidence: 99%